The main directions of banking products promotion in the banking marketing system in Russian commercial banks - Markova O. M. (Interactive science, 2017)
the article is devoted to the research of directions of client-oriented approach application during bank products promotion in Russian banks. Attention is paid to the development of electronic banking, social networks through which consumers receive the necessary information about beneficial offers and special conditions for providing banking services.
Keywords: электронный банкинг; клиентоориентированность; омниканальное обслуживание клиентов; client-oriented; electronic banking; omni-channel customer service